Tumor Microsatellite-Instability Status as a Predictor of Benefit from Fluorouracil-Based Adjuvant Chemotherapy for Colon Cancer - Ribic, Christine M. (2003)
BACKGROUND: Colon cancers with high-frequency microsatellite instability have clinical and pathological features that distinguish them from microsatellite-stable tumors. We investigated the usefulness of microsatellite-instability status as a predictor of the benefit of adjuvant chemotherapy with fluorouracil in stage II and stage III colon cancer. METHODS: Tumor specimens were collected from patients with colon cancer who were enrolled in randomized trials of fluorouracil-based adjuvant chemotherapy. Microsatellite instability was assessed with the use of mononucleotide and dinucleotide markers. RESULTS: Of 570 tissue specimens, 95 (16.7 percent) exhibited high-frequency microsatellite instability. Among 287 patients who did not receive adjuvant therapy, those with tumors displaying high-frequency microsatellite instability had a better five-year rate of overall survival than patients with tumors exhibiting microsatellite stability or low-frequency instability (hazard ratio for death, 0.31 [95 percent confidence interval, 0.14 to 0.72]; P=0.004). Among patients who received adjuvant chemotherapy, high-frequency microsatellite instability was not correlated with increased overall survival (hazard ratio for death, 1.07 [95 percent confidence interval, 0.62 to 1.86]; P=0.80). The benefit of treatment differed significantly according to the microsatellite-instability status (P=0.01). Adjuvant chemotherapy improved overall survival among patients with microsatellite-stable tumors or tumors exhibiting low-frequency microsatellite instability, according to a multivariate analysis adjusted for stage and grade (hazard ratio for death, 0.72 [95 percent confidence interval, 0.53 to 0.99]; P=0.04). By contrast, there was no benefit of adjuvant chemotherapy in the group with high-frequency microsatellite instability. CONCLUSIONS: Fluorouracil-based adjuvant chemotherapy benefited patients with stage II or stage III colon cancer with microsatellite-stable tumors or tumors exhibiting low-frequency microsatellite instability but not those with tumors exhibiting high-frequency microsatellite instability.